2017
DOI: 10.21009/wahana.012/1.2
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Ukuran Perusahaan, Produktivitas, Dan Reputasi Auditor Terhadap Peringkat Sukuk

Abstract: The purpose of this research is to find out the effect between the profitability, firm size, productivity, and auditor reputation toward rating sukuk. Rating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
3
10
0
6
Order By: Relevance
“…This statement is in line with the findings of Elhaj et al (2015) and Borhan & Ahmad (2018). Meanwhile, the findings of Winanti et al (2017) and Melzatia et al (2019) found that profitability does not affect the sukuk rating because the rating agency in conducting an assessment does not only assess the profitability of an issuer, but there are several other factors according to Pranoto et al (2017) one of them is good cash flow management. Companies that have a high level of profitability do not necessarily apply good cash flow management.…”
Section: Profitabilitysupporting
confidence: 71%
See 2 more Smart Citations
“…This statement is in line with the findings of Elhaj et al (2015) and Borhan & Ahmad (2018). Meanwhile, the findings of Winanti et al (2017) and Melzatia et al (2019) found that profitability does not affect the sukuk rating because the rating agency in conducting an assessment does not only assess the profitability of an issuer, but there are several other factors according to Pranoto et al (2017) one of them is good cash flow management. Companies that have a high level of profitability do not necessarily apply good cash flow management.…”
Section: Profitabilitysupporting
confidence: 71%
“…Previous research by Juardi & Sueno (2019) and Muhammad & Biyantoro (2019) has supported the influence of companies on sukuk's rating. Meanwhile, previous research by Utami (2019) and Pranoto et al (2017) found that the firm size cannot affect the sukuk rating.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In line with the research, (Darmawan et al, 2020) testing 86 samples of companies using multiple linear regression concluded that sukuk ratings can be influenced by company profitability. Research that has similar results is (Afiani, 2013;Astuti, 2017;Cahyati & Nurnasrina, 2019;Kartika Hendra Titisari, 2017;Kurniawan & Suwarti, 2017;Muhammad & Biyantoro, 2019;Pebruary, 2016;Pranoto et al, 2017;Tensia et al, 2015;Widowati et al, 2013), while the researchers who found that the profitability ratio had no effect on the sukuk rating were (Malia & Andayani, 2015;Rukmana & Laila, 2020). Based on the literature review above, this study hypothesizes that:…”
Section: Introductionmentioning
confidence: 72%
“…Dengan menambahkan variabel komisaris independen dan leverage dari penelitian Sunarjanto dan Tulasi (2013). Peneliti juga menambahkan variabel reputasi auditor dari penelitian Pranoto, Anggraini, dan Takidah (2017). Alasan peneliti mengambil variabel-variabel tersebut dikarenakan terdapat ketidakkonsistenan hasil penelitian pada penelitian sebelumnya.…”
unclassified